Clinical Optics 2012-2013 (Basic and Clinical Science Course, 2012)
Physical Optics-- Geometric Optics-- Clinical Refraction-- Contact Lenses-- Intracular Lenses-- Telescopes an Optical Intrumennts-- Visión Rehabilitation